The story of Ferdinand - Leaf, Munro, 1905-1976.; Lawson, Robert, 1892-1957 (New York : Viking, 1964)
Ferdinand likes to sit quietly and smell the flowers, but one day he gets stung by a bee and his snorting and stomping convince everyone that he is the fiercest of bulls.
4.1
K-3
K-3
Wilson's Children
School Library Journal
Book Links (A.L.A.)
Keywords: Bulls -- Fiction; Bulls -- Fiction; Spain -- Fiction; Spain -- Fiction